2021
DOI: 10.1111/jcpe.13561
|View full text |Cite
|
Sign up to set email alerts
|

Sleep duration and severe periodontitis in middle‐aged Japanese workers

Abstract: Aim To evaluate the association between sleep duration and severe periodontitis in Japanese workers. Materials and methods This cross‐sectional study included 1130 workers (mean age 43.0 years) who underwent full‐mouth periodontal examinations and health check‐ups and completed a self‐administered questionnaire that included questions on sleep duration. Logistic regression and a restricted cubic spline model were used to analyse the data. Results Severe periodontitis was identified in 6.3% of the study populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 39 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…Prevention and control of the occurrence and development of periodontitis is a pressing concern [12][13][14]. In addition to common risk factors, such as smoking, alcohol consumption, high blood sugar, and high blood pressure [9,[15][16][17][18], the close relationship between diet, sleep, mental health, and periodontitis has become a growing research topic in recent years [19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Prevention and control of the occurrence and development of periodontitis is a pressing concern [12][13][14]. In addition to common risk factors, such as smoking, alcohol consumption, high blood sugar, and high blood pressure [9,[15][16][17][18], the close relationship between diet, sleep, mental health, and periodontitis has become a growing research topic in recent years [19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Regular dental check-ups emerge as a potent protective factor, with individuals neglecting professional oral care facing a 2.54-fold higher risk of periodontitis. This highlights the integral role of preventive dentistry in mitigating periodontal risk and aligns with the concept of early intervention for maintaining oral health [40].…”
Section: Discussionmentioning
confidence: 58%
“…Another study in which a significant relationship was detected between long sleep duration and periodontitis showed that the estimated probability of periodontitis for each hour of more sleep increased by 17% (15). Unlike these studies, the study by Iwasaki et al determined short sleep duration to be correlated with severe periodontitis (13). In another study, sleep deprivation was revealed to be associated with a high prevalence of periodontitis (12).…”
Section: Discussionmentioning
confidence: 96%
“…However, the inconsistency in the results is remarkable (11). Although some research on the subject has revealed a significant correlation between short sleep duration and periodontitis (12,13) and between short sleep duration and gingival health (14,15), other studies have found no significant relationship (11,(16)(17)(18). Among the studies investigating the correlation between sleep quality and periodontitis, there are studies that found (5,19,20) or did not find a significant correlation between poor sleep quality and periodontitis (16,21).…”
Section: Introductionmentioning
confidence: 99%